Potential of air pruned roots of root trainer plants in Hevea brasiliensis - Thomas V; Shankar Sobhana (PLACROSYM XXII. 22nd Biennial Symposium on Plantation Crops: Leveraging Innovation System in Plantation Sector Through Value Addition, 15-17 December 2016, Indian Council of Agricultural Research-Central Plantation Crops Research Institute, Kasaragod, India. Abstracts. p. 125.)
Recently introduced root trainer plants developed in polypropylene cups using coir pith or elephant dung with soil in the ratio 1:1 as potting medium have gained wide acceptance as superior planting material of Hevea brasiliensis both in India and abroad. Germinated seed or budded stumps are planted in the cup and arranged in soil bed by covering one third of the cup with soil. After successful budding followed by maturation of one whorl of leaf, the plants along with the cup are pulled out from the soil, the roots pruned near the drainage hole of the cup and suspended in metallic stand providing all nursery care. This pre-planting cultural operation is termed hardening by which the plant is prompted to produce large number of lateral roots within the cup to cater to the need for further development. Hardening extends to eight weeks in the nursery and during the course air pruned roots develop callus tissue at the apex which is exposed. This callus tissue has unique tissue orientation with immense potential in tissue regeneration when it comes in contact with a favourable medium which can be exploited for modifying the root architecture of rubber. Air pruned roots with callus were allowed to gro into a root elongation tube (RET) filled with potting medium, attached tightly at the bottom of the root trainer cup. The root primordium emerged from the pericycle of the callus with inherent qualities of the parental root, (particularly the birefringent property exhibited by the respective tissue) with an average length of 1.8 cm per day. The modified root core is characterized by 10-12 thick vertical roots, large number of laterals and fine roots with the expected advantages of better anchorage and mining of resources from deeper strata in the soil. The juvenility of the air pruned root callus as an explant in tissue culture is expected to circumvent the problems associated with rooting while using other sources of explants. The scope of air pruned root plugs (callus) in root architecture modification in Hevea is discussed with supporting anatomical evidences.
Keywords: Air pruned roots; Root trainer